Three new ground living pholcid species (Araneae: Pholcidae) from Parque Estadual da Cantareira, São Paulo, São Paulo, Brazil - Machado, Éwerton O.; Yamamoto, Flávio U.; Brescovit, Antonio D.; Huber, Bernhard A. (Zootaxa, 2007)
Three pholcid species (Araneae: Pholcidae) from Parque Estadual da Cantareira, city of São Paulo, Brazil are newly described: Mesabolivar cantharus n. sp., Mesabolivar camussi n. sp., and Tupigea cantareira n. sp. Collection data suggest a preference of the species for ground level habitats. Preliminary data on Tupigea cantareira n. sp. suggest a continuous occurrence of adult individuals throughout the year, with a peak in the rainy season. It also seems that T. cantareira n. sp. prefers the natural (“Mata”) environment over the reforested Pinus area.